A competence-based theory of the firm - Jörg Freiling (Management Revue, 2004)
The research question of the article is: Does the competence-based view, representing a theory of sustaining competitive advantage, offer simultaneously a comprehensive theory of the firm? In order to develop an answer, it appears to be necessary to elaborate the theoretical basis of the competence-based view by delimitating this perspective from the resource-based one. The scrutiny suggests that the competencebased view represents a theory of the firm with other answers than current theories of the firm in use. Moreover, not all the answers of the competence-based view as to the theory of the firm are convincing. Therefore, fundamental weaknesses and shortcomings, which can be dispelled, are pointed out.
Keywords: 650; competence-based view; resource-based view; theory of the firm; isolating mechanisms; open system view; Kernkompetenz; Ressourcenorientierter Ansatz